Integrated platform for structural and functional analysis of terpene synthases of Cannabis sativa - Danielle Wiles; James Roest; Bhuvana Shanbhag; Julian Vivian; Travis Beddoe (PeerJ)
Terpenoids are the largest and most diverse family of natural products. Volatile terpenes from Cannabis sativa are crucial in flavours, fragrances, and pharmaceuticals due to their unique odours and biological activities, including antimalarial, antibacterial, and insecticidal properties. Their synthesis is catalysed by terpene synthase (TPS) enzymes, which perform cyclisation and rearrangement reactions of over 55,000 distinct terpene compounds. However, low catalytic efficiency of C. sativa TPSs limits their use in large-scale commercial production. The complex biochemistry of these reactions is not well understood due to limited enzyme structure information. To address this, we have developed an integrated platform for the systematic expression, purification, enzymatic characterisation, and crystallisation of TPS enzymes from C. sativa. This workflow combines kinetic, thermostability, and structural analyses with a data-mining-informed crystallisation screen that enabled the production of diffraction-quality crystals. As a demonstration of the platform’s utility, ten C. sativa TPS enzymes were functionally characterised, revealing turnover rates (kcat) ranging from 0.0011 to 0.0204 s−1 and diverse substrate specificities, with each enzyme producing a distinct product profile, highlighting the need for systematic characterisation of C. sativa terpene biosynthesis. Our findings provide a framework for the structural and functional study of C. sativa TPSs. The developed platform sets the stage for future metabolic engineering aimed at optimising terpene production for pharmaceutical, pest management, and synthetic biology applications.